Policies and practices for teaching sociocultural diversity : a framework of teacher competences for engaging with diversity - Arnesen, Anne-Lise (Council of Europe Publishing, 2010)
This publication intends to raise discussion about how teacher education, particularly in-service training, can prepare student teachers to become reflective professionals responsive to diversity in schools and classrooms. It addresses the urgent need to develop courses and practical training which stimulate the competence and reflection necessary to enhance inclusive environments where children and young people can learn to live together respecting differences. This work offers an outline of the main principles underpinning work in the diversity area. It also introduces some key concepts related to sociocultural diversity in education while analyzing some challenges in teacher education and development. It identifies policy measures and guidelines for teachers' pre-service training institutions.--Publisher's description.